Pengembangan Zakat Produktif dan Pendampingan Peningkatan Masyarakat Miskin - Rika Fitriani (Kopertais Wilayah XV Lampung, 2022)
The increasing number of poor people in Indonesia shows the various multi-dimensional problems of this nation, to reduce or eliminate this necessary disease must be supported by the whole nation. In Islam, one of the efforts to reduce and eradicate poverty is the existence of zakat law which functions as an equal distribution of wealth. The distribution of zakat for the poor is not only to meet consumptive needs but more than that. From here the pattern of giving zakat to mustahiq is not only consumptive, but can also be productive. Utilization of zakat can be carried out by developing eight asnaf, for example zakat for the poor can be used for public facilities, such as free medical centers, free maternity clinics, manufacturing factories that involve them and others. In its application, the amil zakat institution must be careful in distributing this productive zakat, research on zakat recipients and the types of productive businesses should receive more attention. After that, a trustworthy and professional management also contributed to the success of this program.